Relevancy of Agri-Clinic and Agri-Business Center Training Curriculum for Agripreneurs: A study in Uttar Pradesh - Prashish Singh,; Basavaprabhu Jirli,; Akanchha Kumari,; JAGRITI KUMARI, (Indian Journal of Extension Education, 2025)
The Agri-Clinic and Agri-Business Center (AC&ABC) programis designed to train rural youth in agricultural skills, enabling them to start their own ventures and support farmers. This study was carried out from March to September 2021, analyzed the relevancy of training courses provided under the scheme by nodal training institutes in enhancing entrepreneurial success. A total of 100 respondents from a nodal training institute in Varanasi participated, and Data was gathered using a pre-tested interview schedule following an Ex-Post-Facto research design. Findings revealed that, in the Entrepreneurial Development phase, the relevancy index ranged from 54.34% for "Problem Solving" to 72.67% for "Communication Skills." In the Enterprise Planning and Resourcing phase, scores varied between 58.34% for "Mobilization of Resources" and 78% for "Enterprise Planning." For the Entrepreneurial Management phase, the lowest score was 55% for "Cash/Fund Flow," and the highest was 79% for "Related Case Studies." In the Entrepreneurial Planning phase, the relevancy index ranged from 53.67% for "Market Survey: Report and Analysis" to 81% for "Exposure Visits". Key challenges were social stigma (60%), market fluctuations (59%), pricing (40%), and climate (33%). The study recommends refining AC&ABC training with enriched content, digital literacy, strategy, and experiential learning..